PARAMETRIC MODEL OF LUMBAR VERTEBRA - CAPPETTI Nicola; NADDEO Alessandro; PELLEGRINO Arcangelo; SOLITRO Giovanni Francesco; NADDEO Francesco (Journal of Industrial Design and Engineering Graphics, 2010)
The present work proposes the realization of a parametric/variational CAD model of a normotype lumbar vertebra, which could be used for improving the effectiveness of actual imaging techniques in informational augmentation of the orthopaedic and traumatological diagnosis. In addition it could be used for ergonomic static and dynamical analysis of the lumbar region and vertebral column.